2020
DOI: 10.1093/gbe/evaa126
|View full text |Cite
|
Sign up to set email alerts
|

The Coevolution of Fungal Mitochondrial Introns and Their Homing Endonucleases (GIY-YIG and LAGLIDADG)

Abstract: Fungal mitochondrial (mt) genomes exhibit great diversity in size which is partially attributed to their variable intergenic regions and most importantly to the inclusion of introns within their genes. These introns belong to group I or II, and both of them are self-splicing. The majority of them carry genes encoding Homing Endonucleases, either LAGLIDADG or GIY-YIG. In this study, it was found that these intronic Homing Endonucleases Genes (HEGs) may originate from mt free-standing ORFs which can be found now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 86 publications
(111 reference statements)
5
60
0
Order By: Relevance
“…This would enhance the expression of the IEP as it would benefit from the host genes transcription and translation signals. This would entwine the intron and the HEG that may have started out as independent elements but now coevolve to maintain splicing and homing/mobility activities ( Guha et al, 2018 ; Megarioti and Kouvelis, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would enhance the expression of the IEP as it would benefit from the host genes transcription and translation signals. This would entwine the intron and the HEG that may have started out as independent elements but now coevolve to maintain splicing and homing/mobility activities ( Guha et al, 2018 ; Megarioti and Kouvelis, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…HEs can be encoded by independent free-standing genes or their genes (HEGs) are embedded within intronic sequences. It has been reported that HEGs can move independently from their ribozyme partners ( Mota and Collins, 1988 ), although recent studies suggest that intron-encoded HEG co-evolve with their ribozyme partners ( Megarioti and Kouvelis, 2020 ). Finally, there are instances where group II introns encode HEGs; typically group II introns can be ORF-less or encode reverse transcriptases ( Toor and Zimmerly, 2002 ; Mullineux et al, 2010 ; Hafez and Hausner, 2012 ; Zimmerly and Semper, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second hypothesis suggests more recent intron expansion even between diverse species through horizontal transfer (Gonzalez et al, 1998 ). Both hypotheses could be proven based on the most recent pan genomic approach, which indicated an intron-rich ancestor of fungi as well as the existence of intron-late events through a range of recombinational events that resulted from both vertical and horizontal gene transmissions (Megarioti and Kouvelis, 2020 ). Although mitochondrial introns have been viewed by many as neutral elements (Goddard and Burt, 1999 ) recent studies are suggesting some introns may impact mitochondrial gene expression (Rudan et al, 2018 ), virulence in some fungal pathogens (Baidyaroy et al, 2011 ; Medina et al ), and resistance to certain fungicides (Cinget and Bélanger, 2020 ).…”
mentioning
confidence: 99%
“…A total of two different mobile introns were annotated in the mitogenome of P. fijiensis ( Figure 1 A). All encoding introns were characterized as group I intron type, which encodes homing endonucleases (HE) [ 67 ]. They belonged to the LAGLIDADG family and were 680 bp for an intronic-ORF of 2968 bp length in nad5 and 743 bp long for an intronic-ORF of 1056 bp length in cob ( Figure 1 , Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A variable number of open reading frames of unknown function and introns related to homing endonuclease genes (HEG), often including GIY-YIG or LAGLIDADG protein domains, were found in several Mycosphaerellaceae genomes including P. fijiensis ( Table 2 ; Figure 1 ). Despite not being ubiquitous in Ascomycete mitogenomes these mobile elements are fairly common [ 16 , 17 , 22 , 67 , 70 ]. Differences in mitogenome sizes, gene order and gene duplication among Mycosphaerellaceae are attributed to heterogeneous content of accessory genes, and intron mobile sequences ( Table 1 , Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%